Metaphors in Kaba tuanku lareh simawang story - Muhardis; Yulia Fitrina (JOALL (Journal of Applied Linguistics and Literature), 2023)
This paper discusses the use of metaphor in Kaba Tuanku Lareh Simawang. Using the Metaphor Identification Procedure at Vrije Universiteit (MIPVU) method, this study analyzes the metaphorical expressions found in the text, which was written by Syamsuddin St. Radjo Endah and published by Balai Bahasa Provinsi Sumatra Barat in 2021. This research aims to examine how metaphor is used in the text to reflect human proximity to nature. The findings show that metaphor is employed in the form of phrases and clauses in Kaba Tuanku Lareh Simawang, taking the form of analogies related to human faces, fate, events, and animals. All the metaphors reflect the concepts that are alive and continuously developing in Minangkabau society. Metaphors serve as a reflection of human proximity to nature, following the adage "alam takambang menjadi guru”. The results of this study offer insights into the culture and way of thinking of the Minangkabau people. Metaphors are significant elements of language that represent people's thoughts and cultures. Each culture has its way of using metaphors related to values and experiences considered important in their lives. Thus, understanding the concepts and metaphors in language can provide profound insights into people's thoughts and cultures. In conclusion, this study highlights that the use of metaphor in Kaba Tuanku Lareh Simawang reflects human proximity to nature. Metaphors are powerful tools in language that represent people's thoughts and cultures. Analyzing metaphors in traditional literature can provide a deep understanding of the culture and way of thinking of a society.